WOMENS'S VOLLEYBALL IN BRAZIL: SOME HISTORY UNTIL THE YEARS OF 1950 (Fiep Bulletin - online, 2017)
The present study intends to bring to light some of the trajectory of Brazilian women's volleyball, from its 1910presentation to the 1950s, when the socio-cultural scenario of Brazil already provided incipient conditions for the participation ofwomen in sport. The choice of the study is justified by its importance for the development of Brazilian volleyball, with facts that inthe 1950s inaugurated a decade of great representatively regarding the birth of the phenomenon 'volleyball', in itsinstitutionalized form.